The International Refugee Organisation’s Resettlement Policy – A New Approach of the International Community to the Refugee Problem in Europe: A Case Study of DPs and Refugees from Poland - Sękowski , Paweł (Dzieje Najnowsze, 2023)
The International Refugee Organisation operated between 1947 and 1951 as a UN specialised agency. The IRO’s work was a continuation of the humanitarian actions previously organised for displaced persons (DPs) and refugees by UNRRA and the IGCR. This paper aims to analyse the resettlement policy of the IRO as indicative of the international community’s new approach to handling DPs and refugees, on the example of DPs and refugees from Poland, who constituted the largest national group under IRO care in Europe.